Institutional methods used for organizational processes within public relations in light of standards for developing institutional work - A survey study on government institutions - Omer, Maha Mustafa (Journal of Humanities & Social Sciences, 2021)
The study aimed to identify the institutional methods used for organizational processes within the Public Relations Department in light of the standards for developing institutional work. The sample of the study consisted of (104) members of a number of government institutions, as this study falls within the descriptive research that depends on the survey method by the questionnaire, and among the most important results of the study: The study proved that there are institutional methods used in the organizational processes of public relations and that they are interconnected and integrated to the end In order to achieve the objectives set for the institutional development process in the institutions in which they work, which reflects sustainability, improvement and facing external challenges, we find that the majority of the sample respondents consider that the institutional methods of the organizational processes of public relations are the backbone of institutional and organizational development, where the percentage of those who approve was strongly (19.2%) and approved by a percentage of (31.7%) of the total sample surveyed, provided that the organizational processes and methods used within public relations to develop them for institutional work in the short and long term The study also showed that the organizational processes for public relations and their standards in the development of institutional work within institutions are nothing but a type of administrative development that includes Internal job performance and proper planning, where the results were interpreted by the majority of the respondents sample N agree (39.4%) and strongly agree (19.2%) of the existence of a work environment that uses best administrative practices represented in training and development plans in light of the information revolution for their institutions to develop in line with the career path and work needs. The study also recommended: It is necessary to pay attention to the processes of comprehensive institutional building because it is the nucleus from which the organizational processes used for public relations are based, through review, evaluation and addressing the deficiencies of development plans for institutional work that suffer from weaknesses and deficiencies due to the lack of specialized and qualified competencies to develop and evaluate those plans. In addition to the existence of another body that is concerned with the continuous evaluation and accountability.
Keywords: institutional methods; organizational processes; public relations; standards; institutional work development